2014
DOI: 10.1155/2014/238780
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Neurotransmitters Changes Associated with Tramadol in Streptozotocin-Induced Diabetes in Rats

Abstract: The incidence of diabetes is increasing worldwide. Chronic neuropathic pain occurs in approximately 25% of diabetic patients. Tramadol, an atypical analgesic with a unique dual mechanism of action, is used in the management of painful diabetic neuropathy. It acts on monoamine transporters to inhibit the reuptake of norepinephrine (NE), serotonin (5-HT), and dopamine (DA). The purpose of this study was to evaluate the effects of diabetes on the brain neurotransmitter alterations induced by tramadol in rats, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
25
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 32 publications
8
25
1
Order By: Relevance
“…Changes in neurotransmitter concentrations in STZ-diabetic rats have also been reported by Ezzeldin et al, 11 who demonstrated altered levels of dopamine, noradrenaline (NA), and serotonin (5-hydroxytryptamine; 5-HT) in several brain regions, including the cerebral cortex, hypothalamus and brain stem. These findings suggest that changes in various neurotransmitters may play a role in the pathophysiology of comorbid depression in DM.…”
supporting
confidence: 63%
“…Changes in neurotransmitter concentrations in STZ-diabetic rats have also been reported by Ezzeldin et al, 11 who demonstrated altered levels of dopamine, noradrenaline (NA), and serotonin (5-hydroxytryptamine; 5-HT) in several brain regions, including the cerebral cortex, hypothalamus and brain stem. These findings suggest that changes in various neurotransmitters may play a role in the pathophysiology of comorbid depression in DM.…”
supporting
confidence: 63%
“…While some researchers found reduced release of norepinephrine in the spinal cord in diabetic rats [116] , others have described opposite findings [117] . There is also evidence of diminished norepinephrine levels in supra spinal areas, such as brainstem and thalamus, but higher concentration in the cortex of diabetic animals [118] . Additionally, impaired spinal opioidinduced release of serotonin (5HT) has been demonstrated in diabetic rats, and this finding may be related to opioid hyporesponsiveness in experimental DNP [119] .…”
Section: Brain Plasticitymentioning
confidence: 97%
“…High plasma levels of 5-HT have been reported in patients with T2DM, although its potential effect on insulin secretion is unclear. The release of 5-HT from activated platelets is enhanced, decreasing intraplatelet 5-HT content and resulting in increased plasma levels of 5-HT in patients with diabetes [ 44 ].…”
Section: 5-ht In Diabetes and Diabetic Complicationsmentioning
confidence: 99%